RETRACTED: Technology for the development of foreign language learning motivation among technical students - Kochkarova Elmira; Kiyasova Ra'no; Qodirova Gavhar; Abdujabbarova Malika (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001